Improving Breastfeeding for Homeless Families. Issue 4 (July 2020) - Spatz, Diane L.
Abstract : Women and families experiencing homelessness face many challenges in breastfeeding. Our breastfeeding expert, Dr. Spatz, discusses two programs offered by the University of Pennsylvania to support breastfeeding mothers living in homeless shelters.